Selection and Spread of Artemisinin-Resistant Alleles in Thailand Prior to the Global Artemisinin Resistance Containment Campaign - Talundzic, Eldin (PLoS Pathog, 2015)
The recent emergence of artemisinin resistance in the Greater Mekong Subregion poses a major threat to the global effort to control malaria. Tracking the spread and evolution of artemisinin-resistant parasites is critical in aiding efforts to contain the spread of resistance. A total of 417 patient samples from the year 2007, collected during malaria surveillance studies across ten provinces in Thailand, were genotyped for the candidate Plasmodium falciparum molecular marker of artemisinin resistance K13. Parasite genotypes were examined for K13 propeller mutations associated with artemisinin resistance, signatures of positive selection, and for evidence of whether artemisinin-resistant alleles arose independently across Thailand. A total of seven K13 mutant alleles were found (N458Y, R539T, E556D, P574L, R575K, C580Y, S621F). Notably, the R575K and S621F mutations have previously not been reported in Thailand. The most prevalent artemisinin resistance-associated K13 mutation, C580Y, carried two distinct haplotype profiles that were separated based on geography, along the Thai-Cambodia and Thai-Myanmar borders. It appears these two haplotypes may have independent evolutionary origins. In summary, parasites with K13 propeller mutations associated with artemisinin resistance were widely present along the Thai-Cambodia and Thai-Myanmar borders prior to the implementation of the artemisinin resistance containment project in the region.